KAJIAN PEMBERIAN PAKAN BERBAHAN BAKU LOKAL DENGAN KANDUNGAN PROTEIN BERBEDA TERHADAP PERTUMBUHAN BENIH LELE (Clarias sp.) - Ekadana Putra Sebayang; Siti Hudaidah; Limin Santoso (Journal of Aquatropica Asia, 2020)
Feed is one of the production costs which accounts for 65% of the total production cost of sangkuriang catfish (Clarias sp.) cultivation, so there is a need for alternative feed ingredients that can reduce feed costs. The use of local raw materials in making feed can be an alternative in cultivation activities and is expected to reduce production costs. This study aims to determine the effect of feeding local raw materials with different proteins on the growth of catfish seeds and to analyze the cost of feed production. This research was conducted on March 20 to June 18 2020 at the Integrated Field Laboratory of the Faculty of Agriculture, University of Lampung. The research design used was a completely randomized design with 4 treatments and 3 replications, namely feed A (32%), feed B (30%), feed C (33%) and feed D (36). The data obtained were analyzed by using the ANOVA test and followed by the Duncan test. The parameters observed in this study were absolute weight growth, daily growth rate, feed conversion ratio, survival rate, protein retention, water feed resistance, feed cost analysis and water quality. The results showed that D feed with 36% protein treatment had a significant effect on the feed conversion ratio of sangkuriang catfish. Feed D resulted in the lowest FCR of 0.58.